IMPLEMENTASI KESYARIAHAN PENERAPAN BIAYA ADMINISTRASI AKAD PEMBIAYAAN DI KOPERASI SYARIAH - Nariswari, Jihan Fashura Ilhami; Galuh, Ajeng Kartika (Islamic Economics and finance in Focus, 2024)
State laws that regulate financing administration costs include Regulation of the Minister of Cooperatives Number 12/Per/M.KUKM/IX/2015 and Regulation of the Financial Services Authority Number 29 of 2014. Islamic law refers to the Qur'an and the fatwa of the DSN MUI. BMT generally applies a percentage and can be usury because it does not reflect real administration costs, so it is necessary to review the determination of the nominal so that it is more in accordance with Islamic law. This study aims to analyze how the implementation of the application of sharia administration costs in the BMT Sarana Wiraswasta Muslim Sharia Cooperative. The study was conducted using a qualitative case study method through interviews with informants. The results of the study showed that the cooperative made a breakdown of administration costs so that it reflects the real expenses needed by considering the guarantee, in accordance with the provisions of both Islamic law and state law. This study provides suggestions for the Cooperative to clearly clarify the details of its administration costs so that members become more aware of the importance of maintaining sharia in their transactions.